Laparoscopic hand‐assisted adrenalectomy for tumours larger than 5 cm. (15th November 2018) - Buxton, Jennifer; Vun, Shen H.; van Dellen, David; Wadsworth, Richard; Augustine, Titus
Abstract: Objective: Adrenal surgery remains a distinct surgical challenge. Technical challenges associated with laparoscopic adrenalectomy are tumour size, haemorrhage control and oncological compromise. Hand‐assisted laparoscopic (HAL) adrenalectomy, utilizing a hand‐port device, offers minimally invasive surgery with the advantages and safety of tactile feedback. We aimed to assess the efficacy of HAL for patients requiring adrenalectomy for tumours over 5 cm in size. Context: Hand‐assisted laparoscopic surgery is used in several surgical specialities over totally laparoscopic surgery to manage sizeable pathology, reduce operating time and conversion rates. HAL adrenalectomy is demonstrated in this series as a safe alternative to laparoscopic adrenalectomy for large adrenal tumours. Design: A retrospective analysis of all HAL adrenalectomies performed over 8 years (October 2006‐May 2015) by a single surgeon was performed. This case series is the largest study of this technique. Patients: All patients who were fit for surgery with adrenal tumours (over 5 cm) were included. Analysis: Primary endpoints were overall mortality, operating time, hospital stay, complications and conversion to open surgery. Results: A total of 56 patients underwent the procedure. A total of 43 had unilateral and 13 bilateral lesions. Most lesions (45) were histologically benign. These included functioning and non‐functioning tumours. Median tumour size was 8 cm (range 5‐19 cm). There was one (1.8%) intra‐operative conversion and no peri‐operative mortality. Postoperative complications occurred in 8 (14%) patients, all self‐limiting. The median length of stay was 6 days (range 2‐21). There was one recurrence of pathology with repeat surgery. Conclusion: Hand‐assisted laparoscopic surgery offers a safe reproducible approach to adrenal surgery combining minimally invasive surgery with tactile integration. Although previously described in small numbers, this represents the largest case series to date. HAL is a safe minimally invasive surgical option for larger tumours, including malignancies. The HAL technique may additionally offer a shorter learning curve for trainee adrenal surgeons.